2012
DOI: 10.1371/journal.pone.0049233
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Ultrasonic Vocalization of Cadherin-6 Knockout Mice

Abstract: BackgroundAlthough some molecules have been identified as responsible for human language disorders, there is still little information about what molecular mechanisms establish the faculty of human language. Since mice, like songbirds, produce complex ultrasonic vocalizations for intraspecific communication in several social contexts, they can be good mammalian models for studying the molecular basis of human language. Having found that cadherins are involved in the vocal development of the Bengalese finch, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…First, as we report, it is very rarely emitted during mating interactions, which is the most common method for collecting adult vocalizations. Second, many studies utilize a high pass filter when analyzing adult vocal data to reduce the interference of high amplitude noise that is generated at low frequencies when animals move through bedding (20 kHz: Nakagawa et al, 2012 ; 35 kHz: Chabout et al, 2015 ; 35 kHz: Hammerschmidt et al, 2015 ). These filters would remove the MFV from analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as we report, it is very rarely emitted during mating interactions, which is the most common method for collecting adult vocalizations. Second, many studies utilize a high pass filter when analyzing adult vocal data to reduce the interference of high amplitude noise that is generated at low frequencies when animals move through bedding (20 kHz: Nakagawa et al, 2012 ; 35 kHz: Chabout et al, 2015 ; 35 kHz: Hammerschmidt et al, 2015 ). These filters would remove the MFV from analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with other vocal categories is more difficult. For example, different studies have used a wide range of maximum durations to characterize a USV as being “short,” from 5 ms (Scattoni et al, 2008 , 2009 ; Grimsley et al, 2011 ; Nakagawa et al, 2012 ) or 10 ms (Branchi et al, 1998 ), up to 50 ms (Enard et al, 2009 ; Chabout et al, 2012 ). Varying this inclusion criterion results in short vocalizations making up a small proportion of the USV repertoire (Scattoni et al, 2008 ; Grimsley et al, 2011 ) or the majority (Enard et al, 2009 ; Chabout et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of N-cadherin function results in severe defects in cortical layer formation and synapse formation and function (Bozdagi et al, 2000;Togashi et al, 2002;Kadowaki et al, 2007). By contrast, mice with mutations in type II cadherins show defects in restricted areas (Manabe et al, 2000;Suzuki et al, 2007;Osterhout et al, 2011;Williams et al, 2011;Nakagawa et al, 2012), even though the cadherins are broadly expressed in the brain. As discussed above, type II cadherins may show strong functional redundancy (Lefkovics et al, 2012).…”
Section: Cadherin Expression and Implications For Functional Redundanmentioning
confidence: 99%
“…Among them, type II classic cadherins are expressed in some restricted populations of neurons that are synaptically connected with each other, suggesting their involvement in synaptic function and the formation of functional neural circuits (Suzuki et al, 1997). Indeed, gain-and loss-offunction analyses have now revealed that type II cadherins play various roles in the development of neural circuitry and mature synaptic function (Manabe et al, 2000;Inoue et al, 2001;Price et al, 2002;Treubert-Zimmermann et al, 2002;Suzuki et al, 2007;Barnes et al, 2010;Matsunaga et al, 2011b;Osterhout et al, 2011;Williams et al, 2011;Nakagawa et al, 2012). Furthermore, genes encoding several type II cadherins have been implicated in the pathogenesis of human psychiatric disorders (Hirano and Takeichi, 2012;Redies et al, 2012).…”
mentioning
confidence: 99%
“…As songbirds, Cdh6 expression is broadly seen in vocal control areas of the mouse brain (Figure 2; [19] and our unpublished data). Cdh6 knockout mice showed abnormal USVs, with high pitch for an isolation call and a courtship song [47]. Since other vocalizations such as aggressive calls are intact, vocalization defects in Cdh6 mutant mice seem to be specific for USVs.…”
Section: Role Of Cadherins In Vocal Behaviorsmentioning
confidence: 98%